The Effect of Domestic Consumption on Natural Rubber Farmgate Price in Indonesia - Pramananda, Penggawa Pietra; Rifin, Amzul; Nauly, Dahlia (Universitas Muhammadiyah Yogyakarta, 2022)
The decline in natural rubber farmgate prices in recent years directly impacted Indonesia’s natural rubber market. In response to this phenomenon, the government plans to increase natural rubber domestic consumption to raise Indonesia’s rubber price. This study aimed to determine the effect of increasing natural rubber domestic consumption on natural rubber farmgate prices and analyze other factors those influence it. The Error Correction Model was used to identify the variables that significantly affect Indonesia’s natural rubber farmgate price. The data used in this study were monthly data from January 2012 to December 2017. Results showed that natural rubber domestic consumption did not significantly affect the Indonesia natural rubber farmgate price. However, in the long run, Indonesia’s natural rubber farmgate price was influenced by the previous period of Indonesia’s natural rubber prices, world natural rubber prices, world crude oil prices, and exchange rates. While in the short run, Indonesia’s natural rubber farmgate price was influenced by the previous period of Indonesia’s natural rubber prices, world natural rubber prices, and exchange rate.